Operability and Optimum Control of the MEG Bench Scale and Distillation Plant - Al-Ajooli, Samer Ata Qasim (Curtin University, 2019)
The sponsored bench-top scale mono-ethylene glycol pilot plant located at Curtin University was designed and operated to use realistic production fluids such as formation water/brine and condensate mixture to simulate conditions representative industrial MEG system. To achieve the optimum operating conditions, the performance results of MEG pre-treatment system has been thoroughly investigated in terms of emulsion tendencies, switchover between corrosion management strategies and alkalinity control.